A review of the genus Chrysomphalus Ashmead (Hemiptera: Coccoidea: Diaspididae) with descriptions of a new species and a new, related genus - Smith-Pardo, Allan H.; Evans, Gregory A.; Dooley, John W. (Zootaxa, 2012)
The taxonomy of the genus Chrysomphalus Ashmead (Diaspididae: Aspidiotinae) is reviewed. A new monotypic genus of armored scale, Pentalaminaspis Smith-Pardo, Evans and Dooley, is described and illustrated with Chrysomphalus minutus Kotinsky, 1908 as the type species. A new species, Chrysomphalus nepenthivorus Smith-Pardo, Evans & Dooley, is described and illustrated. This species was intercepted at a U.S. port of entry on hybrids of pitcher plants (Nepenthes) originating from Thailand. Chrysomphalus greeni Leonardi, 1914 is transferred to the genus Melanaspis and Chrysomphalus degeneratus Leonardi, 1896 is transferred to the genus Diaspidiotus. A discussion and key to species of the genus Chrysomphalus are provided as well as a key to aspidiotine genera similar to Chrysomphalus.